Rekomendasi Cerdas Destinasi Wisata di Kabupaten Jember - wulandari, diah ayu retnani (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2025)
Tourism is all forms of object creation, tourism business and tourism attractions. The tourism sector in Indonesia is currently growing very rapidly. The development of the tourism sector causes an increase in tourism visitors which will also have an impact on increasing foreign exchange, but there are several obstacles in the tourism sector, one of which is the availability of information. Information regarding tourist attractions for tourists is very important so that tourists do not choose the destination of these tourist attractions, especially tourists who have never visited the area. Information regarding tourist attractions is still lacking and they still have to search one by one to get this information. Therefore, we need a tourism recommendation system that can be a means of seeking information and can obtain the results of these tourism recommendations in a system that suits the needs of the tourists themselves.